H2S and NOx tolerance capability of CeO2 doped La1−xCexCo0.5Ti0.5O3−δ perovskites for steam reforming of biomass tar model reaction. (January 2019) - Ashok, J.; Das, S.; Dewangan, N.; Kawi, S.
Graphical abstract: Highlights: La1−x Cex Co0.5 Ti0.5 O3 perovskites were studied for tar reforming reaction in the presence of H2 S and NOx compounds. La0.8 Ce0.2 -Co0.5 Ti0.5 O3 catalyst displayed stable catalytic performance in the presence of 500 ppm of NO. Upon poisoning with 50 ppm of H2 S, 90% of catalysts activity can be regenerated. Better activity for La0.8 Ce0.2 -Co0.5 Ti0.5 O3 catalyst is due to higher amount of surface Co species and oxygen vacancies. CeO2 -doping to perovskites enhanced surface O2 mobility and vacancies. Abstract: In this paper, the La1−x Cex Co0.5 Ti0.5 O3−δ perovskite materials were explored for steam reforming of biomass tar (SRT) reactions using toluene as a model compound at various steam-to-carbon conditions. The perovskite materials were also investigated for steam reforming reaction at 750 °C and 700 °C, respectively in the presence of poisonous compounds such as H2 S and NOx. The role of Ce-doping to La1.0 -Co0.5 Ti0.5 O3 material catalytic performances was also investigated. Among all the catalysts, catalyst composition of La0.8 Ce0.2 -Co0.5 Ti0.5 O3 displayed a stable toluene conversion of around 90% at 700 °C and S/C of 2 for a period of 22 h tested in toluene reforming reaction. Additionally, La0.8 Ce0.2 -Co0.5 Ti0.5 O3 catalyst displayed stable SRT performance in the presence of 500 ppm of NOx. On the other hand, by introducing 50 ppm of H2 S during SRT reaction at 750 °C, all the catalysts showed deactivation behaviour. At the same reaction temperature regeneration of about 90% of activity was observed for La0.8 Ce0.2 -Co0.5 Ti0.5 O3 catalyst. Overall, the best catalytic performance of La0.8 Ce0.2 -Co0.5 Ti0.5 O3 catalyst is due to the availability of higher amount of surface Co species and oxygen vacancies than other catalysts. From XRD analysis of calcined, reduced and spent catalysts, the presence of perovskite structural phase was observed for all the La-based catalysts and negligible Co species agglomeration observed during SRT reaction. CO2 -TPD studies showed that the basicity of La0.8 Ce0.2 -Co0.5 Ti0.5 O3 and La1.0 Co0.5 Ti0.5 O3 catalysts was higher compared to other perovskite compositions. TGA and Raman analysis revealed, suppressed rate of carbon deposition for all the Ce-contained materials and the deposited carbon was mostly amorphous in nature. Finally, low carbon deposition rate and high surface oxygen mobility were the possible reasons for La0.8 Ce0.2 -Co0.5 Ti0.5 O3 catalyst's stable catalytic performance over other catalysts.